2018
DOI: 10.14687/jhs.v15i1.5268
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between right hand finger ratio (2D:4D) and the parameters of anthropometric and physical fitness in children

Abstract: It is hypothesized that there is a correlation between the ratio of second hand finger to fourth hand finger (2D:4D) which is an indicator of prenatal testosterone and physical fitness and sportive performance The aim of this study was to determined correlation between the right hand finger ratio (2D:4D) and the parameters of anthropometric and physical fitness in male and female children aged between 10 and 12. Six hundred and seventy eight males whose age average was 0.49±1.32 and 592 females whose age avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…It is important to acknowledge that muscular fitness is a multidimensional construct, and while it is specific to the muscle group, type of muscle action, muscle contraction, contraction velocity, equipment, and joint range of motion, we only included studies that measured muscular fitness using HGS. Several studies have examined relationships for other measures of muscular fitness, including lower body absolute strength (Eler, 2018a;Folland et al, 2012), upper body relative strength (Eklund et al, 2020;Güler, 2018;Kociuba et al, 2017;Kozieł et al, 2017), both lower body power (Eler, 2018a;Güler, 2018;Gümüs ¸& Tutkun, 2018;Hsu et al, 2018;Kociuba et al, 2017;Kozieł et al, 2017) and upper body power (Cho, 2020), and abdominal/core endurance (Kociuba et al, 2017;Kozieł et al, 2017). Collectively, most studies (Cho, 2020;Eklund et al, 2020;Eler, 2018a;Güler, 2018;Hsu et al, 2018;Kociuba et al, 2017;Kozieł et al, 2017) found that 2D:4D was a negligible-tomoderate negative correlate of other measures of muscular fitness, which broadly supports our results.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to acknowledge that muscular fitness is a multidimensional construct, and while it is specific to the muscle group, type of muscle action, muscle contraction, contraction velocity, equipment, and joint range of motion, we only included studies that measured muscular fitness using HGS. Several studies have examined relationships for other measures of muscular fitness, including lower body absolute strength (Eler, 2018a;Folland et al, 2012), upper body relative strength (Eklund et al, 2020;Güler, 2018;Kociuba et al, 2017;Kozieł et al, 2017), both lower body power (Eler, 2018a;Güler, 2018;Gümüs ¸& Tutkun, 2018;Hsu et al, 2018;Kociuba et al, 2017;Kozieł et al, 2017) and upper body power (Cho, 2020), and abdominal/core endurance (Kociuba et al, 2017;Kozieł et al, 2017). Collectively, most studies (Cho, 2020;Eklund et al, 2020;Eler, 2018a;Güler, 2018;Hsu et al, 2018;Kociuba et al, 2017;Kozieł et al, 2017) found that 2D:4D was a negligible-tomoderate negative correlate of other measures of muscular fitness, which broadly supports our results.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence between the 2D:4D index and the anthropometric parameters discussed in this paper are consistent with the results of the research conducted so far. Eler (2018) showed correlations between the 2D:4D index and the relative fat level in women, not men. In one of the latest research it was found negative correlation between 2D:4D finger length and muscle mass in girls aged 6-13 years (Pruszkowska-Przybylska et al 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Newer research results indicate a relation between the digit length ratio (2D:4D) of the left hand with the risk of breast cancer in women (Muller et al 2012). On the other hand, Eler (2018) showed correlations of body height and body fat content with the 2nd and 4th finger length quotient in the left hand in women.…”
Section: Discussionmentioning
confidence: 94%
“…Concretamente, Agha-Alinejad et al 2019concluyeron que existía una relación directa entre la ratio 2D:4D y el porcentaje de masa grasa (r=,132; p<,05) en niñas con una edad ligeramente inferior (8-12 años). Respecto a la relación entre la ratio y el IMC, estudios previos mostraron también una relación directa (Eler, 2018;Ranson et al, 2015), sumado al de otras variables como la estatura y la circunferencia de cintura, no existiendo relación en el caso de los niños (Ranson et al, 2015), en línea con los resultados del presente estudio. Esta relación directa entre la ratio 2D:4D y la masa grasa puede ser debida a que los estrógenos estimulan la multiplicación de las células grasas (Mauras et al, 2015), lo que apoyaría los resultados obtenidos, donde un mayor ratio 2D:4D se relaciona con una mayor porcentaje de grasa.…”
Section: Discussionunclassified
“…Estudios previos, mostraron que las personas con mayores ratios 2D:4D, presentaban un mayor porcentaje de grasa corporal (Agha-Alinejad, Farzad, Akbari, Moffit, & Dakhili, 2019;Eler, 2018). También se ha analizado la relación entre la ratio 2D:4D y diferentes parámetros antropométricos como la altura, el peso, el índice de masa corporal (IMC), la circunferencia de la cintura (Eler, 2018;Erkec, 2019;Ranson, Stratton, & Taylor, 2015) y la relación cintura-pecho (Fink, Neave, & Manning, 2003). En líneas generales, la mayoría de autores informan de la existencia de una relación directa entre la ratio y el IMC, pero inversa entre la ratio y la altura.…”
Section: )unclassified